THE INFLUENCE OF TIMELINESS AND E-SERVQUAL ON CUSTOMER SATISFACTION WITH THE DELIVERY SERVICE PT. JALUR NUGRAHA EKAKURIR (JNE) EXPRESS (CASE STUDY OF JNE EXPRESS MINDI CUSTOMERS IN NORTH JAKARTA) - Putri Anggraini; Ai Netty Sumidartiny (JAMBIS : Jurnal Administrasi Bisnis, 2021)
This study aims to determine and analyze the effect of timeliness and e-servqual on customersatisfaction with the delivery service of PT Lintas Nugraha Ekakurir (JNE) Express. The data usedwas primary data which was collected through the distribution of questionnaires with a Likertscale. The population in this study was 1,844,462 residents of North Jakarta. With accidentalsampling technique, a sample of 100 respondents was obtained from the population. This studyused a quantitative approach. Calculations and data analysis were performed using SPSS 28.0.The results showed that partially (t test) Punctuality (X1) has a significant effect on CustomerSatisfaction (Y) as evidenced by tcount> ttable (4.234 > 1.984) and the coefficient of determination(r2) of 43.5%. Partially (t test) E-Servqual (X2) has a significant effect on Customer Satisfaction(Y) as evidenced by tcount> ttable (8.743 > 1.984) and the coefficient of determination (r2) of 62.6%.Simultaneously (f test) Punctuality (X1) and E-Servqual (X2) have a significant effect on CustomerSatisfaction (Y) as evidenced by fcount> ftable (104.963 > 3.09) and the coefficient of determination(r2) of 68.4%.